What is the contribution of different business processes to material circularity at company-level? A case study for electric vehicle batteries - Schulz-Mönninghoff, Magnus; Neidhardt, Michael; Niero, Monia (Journal of cleaner production, 2023)
With the growth of electric mobility, automotive manufacturers are nowadays facing the challenge of implementing a Circular Economy (CE) for electric vehicle (EV) batteries. Meanwhile, no consensus exists on how to assess material circularity and assign responsibilities across different business processes of the organization. To address this gap, the present study uses an illustrative case study of an automotive manufacturer seeking to improve the material circularity of its’ electric vehicle battery portfolio. Following a 3-step framework inspired by the British Standard BS 8001:2017, we investigate how business processes in relation to product development, supply chain, production, end-of-life and business models can contribute to the material circularity of EV batteries in different scenarios. Among the key contributions, the study firstly provides guidance for companies on how to model material circularity for batteries at company-level based on EV market projections. Secondly, our findings show that by combining a closed-loop production with different end-of-life strategies such as remanufacturing, repurposing and recycling, automotive manufacturers can increase material circularity for critical battery materials from 5% today to 23% by 2030. Thirdly, we specify how different business processes can contribute to increasing material circularity, including a) which business processes collaborate, b) the affected material streams (i.e. inflow or outflow), c) through which activities and d) to what extent, i.e. the impact on the quantitative results for material circularity. Based on the findings, we discuss limitations of the study and derive pathways for future research on how to assist companies in an accelerated transition towards a CE. •Assessment of material circularity for electric vehicle batteries at company-level.•Analysis of four scenarios, which are developed based on a 3-step framework.•Application of Circular Transition Indicator and Material Circularity Indicator.•Material circularity of 23% possible for key battery materials by 2030.•Specification of contributions by business processes at automotive manufacturers.